EFFECT OF WETTING / DRYING CYCLES ON THE SWELLING POTENTIAL OF ANKAWA ALLUVIAL SEDIMENTS - Khidir Khalaf, Fawzi; Ali Abbas, Hasan (Journal of Madenat Alelem University College, 2023)
This research deals with the phenomenon of swelling in local clayey soil in Iraq, which is characterized as a sedimentation region rich in various ions that aid in the formation of clay soil. The mineral composition of the clay particles is one of the main factors that affect the soil’s swelling. The soil studied is brown clay soil, classified according to the Unified Soil Classification System (USCS) as clay soil with low plasticity (CL), containing approximately 35-40% clay materials. The test results for undisturbed samples, with an initial moisture content of 14% and dry density equal to 16.5 kN/m3, indicate that the swelling percentage starts to decrease significantly in the first cycle, reaching 6.8%. Subsequent cycles further reduce the swelling until it stabilizes in the fifth cycle at a ratio of 3.4%. This reduction in swelling is attributed to the shrinkage of the soil during drying, which affects the soil structure and arrangement of particles, transforming the soil structure into a flocculated state. This alteration occurs during the first five cycles, after which the swelling behavior stabilizes in the sixth and seventh cycles. The swelling pressure also decreases with an increase in the number of cycles, reaching stability around the fifth cycle. The most significant change in pressure occurs during the first cycle, with a decrease of 15.9% compared to the initial pressure. The pressure then gradually decreases until reaching 136 kN/m2 in the fifth cycle, representing a reduction of approximately 30.25%. These results are significant for estimating the swelling pressure and volume change of clayey soil.